1981
DOI: 10.1149/1.2127501
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and In Situ Laser Raman Spectroscopy Studies on Carbon‐Supported Iron Phthalocyanine Electrodes

Abstract: Cyclic voltammetry has been used to characterize the electrochemical behavior of iron phthalocyanine false(normalFePcfalse) films on glassy carbon electrodes in 0.05MH2SO4 solution. The films were found to catalyze oxygen reduction but deactivate on continuous cyclic scans. Films prepared by evaporation of a solution containing normalFePc and organic solvents, as well as by immersion in such a solution, showed significantly higher activity than those prepared by vapor deposition. This difference was attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…FePc films prepared by evaporation of a solution containing FePc and organic solvents as well as by immersion in such a solution show significantly higher activity than those prepared by vapor deposition [121]. The difference was attributed to the difference in the polymorphic forms of the FePc films.…”
Section: Co-and Fe-based Phthalocyanines (Pc)mentioning
confidence: 94%
“…FePc films prepared by evaporation of a solution containing FePc and organic solvents as well as by immersion in such a solution show significantly higher activity than those prepared by vapor deposition [121]. The difference was attributed to the difference in the polymorphic forms of the FePc films.…”
Section: Co-and Fe-based Phthalocyanines (Pc)mentioning
confidence: 94%
“…Coordination of platinum to the carbon-carbon triple bond of poly(buta-1,3-diynyl-1,3phenylene) offered a convenient method of dispersing platinum at an atomic level along the glassy carbon precursor, and, under the most optimistic of scenarios, offered a method of dispersing platinum at the atomic level in the glassy carbon solid itself. Scheme9 shows the synthetic strategy for the preparation of catena-[ poly(buta-1,3-diynyl-1,3-phenylene)]bis(triphenylphosphine)platinum(O) (38). The synthesis makes use of the known lability of alkene ligands coordinated to platinum towards displacement by acetylenes. '…”
Section: Synthesis Of Nanoscale Clusters Of Platinum In Glassy Carbonmentioning
confidence: 99%
“…The cathodic waves (Ic, IIc, and IIIc) are hardly evident during the first cathodic scan. Our previous studies (10) also showed that the appearance of these waves is independent of the method of preparing the film, and, hence, we have ruled out the possibility that they are due to impurities or to an effect of pyridine on the FePc. As can be seen, the peaks are very synunetrical, characteristic of reactants confined to the electrode surface, The integrated charges under each peak are in the order of ,,300 ~C/cm 2 which correspond to less than 1 monolayer coverage.…”
Section: Cathodic Behavior Of Fepc Films Supported On Goldmentioning
confidence: 71%
“…This well-defined wave is, however, observed only on the first scan, and its intensity is reduced gradually on subsequent cyclic scans. We have termed this phenomenon as "deactivation" (10). Some of the intensity of the O2 reduction wave can be recovered by leaving the electrode in solution at open circuit for more than 1 hr.…”
Section: Rtmentioning
confidence: 99%
See 1 more Smart Citation